Eksistensi Penyelesaian Sengketa UMKM Secara Non Litigasi di Desa Bandar Labuhan - Meher, Montayana; Ramadhan, M. Citra; Suharyanto, Agung; Silviana, Dini; Ardhana, Salsa Novia; Putri, Ade (Universitas Medan Area, 2024)
This community service aims to enhance the understanding of the community in Bandar Labuhan Village regarding the non-litigation resolution of Micro, Small, and Medium Enterprises (MSMEs). The implementation method involves counseling activities covering the understanding of rights and obligations in the context of MSMEs, along with non-litigation dispute resolution mechanisms. The results reflect a positive impact, including increased legal awareness and active community participation. However, challenges and disagreements in implementing these mechanisms are also indicated. The discussion includes an analysis of success and potential obstacles. Acknowledging challenges as natural hurdles, suggestions for advanced approaches such as mentoring or additional training are proposed. The evaluation results provide profound insights for developing future community service programs, emphasizing material adjustments and a more focused approach. In conclusion, this community service affirms the success of increasing community understanding through counseling activities, but the challenges require a sustainable approach. Future program development is expected to be more effective in responding to community needs and contextual changes regarding the non-litigation resolution of MSME disputes.